IMPLEMENTASI SISTEM MANAJEMEN PENGETAHUAN UNTUK DISTRIBUSI BANTUAN LOGISTIK KORBAN BENCANA ALAM - H. Ary Setyadi STMIK AUB Surakarta; Robby Rachmatullah . (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2017)
ABSTRACT - Logistics distribution to victims of catastrophe is often currently experiencing problems. Distribution was sub-standard nutrition or health and living standards, inter-regional distribution uneven and the number of each type of aid that do not meet several criteria. In this study, the distribution logistics management disaster will be a data base management system used to manage logistics data and it’s distributing. From all the data managed a technique made the decision makers on the status of all kinds of related logistics. The system will also to provide services in determining the type and amount of logistical requirements needed for disaster victims in each village or region. The technique used to create the model is applied to Operations Research where both types of logistics and estimated number of each type of each generated using Linear ProgrammingKeywords : knowledge management, logistical assistance, disaster victims